Early mechanical changes of limb muscle in septic shock assessed by dual-plane shear-wave elastography - Ivo Neto Silva; Rui Azevedo; Joana Duarte; Stanislas Abrard; José Alberto Duarte; Karim Bendjelid (Intensive Care Medicine Experimental, 2026)
Abstract Background Septic shock induces skeletal muscle wasting and neuromuscular dysfunction, contributing to ICU-acquired weakness (ICUAW) and poor recovery after critical illness. Conventional ultrasound primarily captures structural changes but provides limited insight into early muscle mechanical alterations or their relationships with clinical factors. Shear-wave elastography (SWE) enables non-invasive assessment of muscle stiffness, but its performance in critically ill patients remains poorly understood. Methods In this prospective study, adults with septic shock requiring invasive ventilation underwent daily muscle ultrasound during the first five ICU days. Rectus femoris muscle cross-sectional area, echogenicity and SWE-derived shear modulus (SM RF ) were assessed bilaterally using conventional ultrasound and shear-wave elastography in both longitudinal and transverse orientations at two anatomical sites within the rectus femoris . An exploratory anisotropy estimate was derived from the transverse-to-longitudinal stiffness ratio. ICUAW was evaluated at the time of extubation. Associations between ultrasound markers and clinical variables were explored using correlation and regression analyses. Results Twenty-seven patients (66.7% male, mean age 61 ± 12 years) were analysed (125 sessions, 4,971 images). Rectus femoris cross-sectional area declined from 3.90 cm² on Day 1 to 2.97 cm² by Day 5 (− 21%, p < 0.01), while echogenicity remained stable. Shear modulus (SM RF ) demonstrated region- and orientation-dependent behaviour. At the lower-third region, longitudinal SM RF remained relatively stable (7.08 to 7.72 kPa), whereas transverse SM RF declined significantly (15.20 to 12.30 kPa, p = 0.009), resulting in dynamic changes in the transverse-to-longitudinal stiffness ratio. Muscle atrophy trajectories were similar in patients with and without ICUAW, and no significant between-group differences in SM RF measures were identified. Higher illness severity (SOFA score, β = 18.18, p = 0.003) and cumulative fluid balance (β = 3.32, p = 0.002) were associated with increases in longitudinal SM RF . Greater early caloric intake (β = 0.076, p = 0.006) and increases in echogenicity (β = −0.91, p = 0.027) were associated with changes in transverse SM RF . Conclusions Rapid muscle loss during early septic shock was accompanied by distinct, site- and direction-specific stiffness changes. Dual-plane SWE identified early mechanical changes, although these measures did not discriminate ICUAW status in this cohort. Associations with clinical variables suggest that SWE may help capture early physiological muscle changes in critical illness.